Effect of notch depth on fracture toughness of Y-TZP and determination of its actual value. Issue 1 (January 2015) - Zhao, Wei; Peng, Cheng; Lv, Ming; Bai, Mingmin; Rao, Pinggen
Abstract: Femtosecond lasers were used to cut ultra-sharp V-notches ( ρ <0.5 µm) on the yttrium-stabilized tetragonal zirconia polycrystal (Y-TZP). The actual fracture toughness of Y-TZP ceramics is 4.4 MPa/m 1/2 measured by SEVNB method. As comparison, the fracture toughness values of Y-TZP samples with different U-groove width were measured by SENB method. The fracture toughness value with U-groove width of 200 µm is 13.1 MPa/m 1/2, which is about 3 times than the value with ultra-sharp V-notch. In addition, fracture toughness values of the Y-TZP ceramics with different notch depth were studied. To obtain the actual fracture toughness of Y-TZP ceramics with ultra-sharp V-notch, the ratio of notch depth to sample height ( a / W ) should be controlled in 0.25–0.6.